Flexible Reports in Ericsson MSDP - Krantz, Robert; Björkman, Patrik (My University, 2010)
Report Viewer in the Ericsson MSDP is in its current form not being used as intended. Customers of the system only extract data from it to then use in their favorite data visualization tool. Additionally, a lot of users who would benefit from using Report Viewer avoid it thinking it is too hard to use. The task of this project is to evaluate other existing reporting systems and choose one to build a working prototype from. This prototype should allow users to both view and create their own reports and should accommodate the current users of the system, but also users who have no previous experience from using Report Viewer. During evaluation both commercial and free reporting systems were looked at and in the end four were considered for use in the final prototype, BIRT being the one eventually chosen. Designing and prototyping was done in iterations in order to exclude as many usability problems as possible and each iteration was tested on a set of test users. In the end a web based prototype built on the BIRT report engine was implemented and tested.
Keywords: Information Technology; Informationsteknik